Good Public Governance in Islamic Perspective: An Analysis on the World Governance Indicator in OIC Member Countries - Muhammad Ghafur Wibowo (Universitas Ahmad Dahlan, 2020)
This study seeks to reveal the suitability of Islamic teachings with Good Public Governance (GPG), which in recent decades, has become a concern of various countries in the world. By exploring many reputable references, it is known that there is a match between the governance index published by the World Bank and the teachings of Islam. Practically even OIC has made the issue of good public governance represented by the governance index as a common goal of all its members. However, the facts show that the governance index in various OIC member countries is still relatively low compared to other countries. Therefore, all OIC member countries need to enhance further the implementation of Islamic teachings in the management of the country to produce better governance.